The Added Years Elderly in India and Kerala - Leela Gulati S Irudaya Rajan (Economic and Political Weekly October 30, 1999, 1999)
While ageing of the population represents demographic achievements in lowering birth and death rates, it also poses challenges in care of the elderly. The experience of Kerala is instructive for the rest of India as Kerala is a few years ahead on the demographic path. This article analyses data on ageing, gender differentials in ageing and widowhood